STRUCTURED HEALTH EDUCATION ON SELF-CARE MANAGEMENT TOWARD SELF-EFFICACY, STRESS AND QUALITY OF LIFE IN HEMODIALYSIS PATIENTS: A QUASI-EXPERIMENTAL STUDY - Netti Herawati; Khamida; Chilyatiz Zahro; Nursalam; Lono Wijayanti; Yurike Septianingrum (Universitas Kadiri, 2026)
Hemodialysis patients face complex issues, including decreased self-efficacy, high stress levels, and diminished quality of life. Comprehensive interventions are required to enhance patients' self-management capabilities. This study aims to analyze the effect of structured self-care management health education based on peer group support on the self-efficacy, stress, and quality of life of hemodialysis patients. This quasi-experimental study used a pre-post test control group design involving 70 respondents (35 intervention, 35 control) selected via consecutive sampling. The intervention group received four sessions of structured health education based on peer support. Research instruments included a self-efficacy questionnaire, the Depression Anxiety Stress Scales (DASS-42), and the KDQOL-SF 1.3. Data were analyzed using Paired T-Test and Mann-Whitney tests. There were significant increases in self-efficacy (p=0.006) and quality of life (p=0.000), as well as a significant decrease in stress levels (p=0.027) within the intervention group. In contrast, the control group showed no significant changes across the three variables (p > 0.05). Peer group support proved effective in facilitating the exchange of experiences and emotional support, which strengthened patients' self-belief in managing their condition. Structured self-care management health education based on peer group support is effective in improving self-efficacy and quality of life while reducing stress levels in hemodialysis patients. This intervention is recommended as an integral part of supportive nursing care in hemodialysis units.